Independent Generation and Time‐Resolved Detection of 2′‐Deoxyguanosin‐N2‐yl Radicals. Issue 32 (2nd June 2020) - Zheng, Liwei; Dai, Xiaojuan; Su, Hongmei; Greenberg, Marc M.
Abstract: Guanine radicals are important reactive intermediates in DNA damage. Hydroxyl radical (HO . ) has long been believed to react with 2′‐deoxyguanosine (dG) generating 2′‐deoxyguanosin‐N1‐yl radical (dG(N1‐H) . ) via addition to the nucleobase π‐system and subsequent dehydration. This basic tenet was challenged by an alternative mechanism, in which the major reaction of HO . with dG was proposed to involve hydrogen atom abstraction from the N2‐amine. The 2′‐deoxyguanosin‐N2‐yl radical (dG(N2‐H) . ) formed was proposed to rapidly tautomerize to dG(N1‐H) . . We report the first independent generation of dG(N2‐H) . in high yield via photolysis of 1 . dG(N2‐H) . is directly observed upon nanosecond laser flash photolysis (LFP) of 1 . The absorption spectrum of dG(N2‐H) . is corroborated by DFT studies, and anti ‐ and syn ‐dG(N2‐H) . are resolved for the first time. The LFP experiments showed no evidence for tautomerization of dG(N2‐H) . to dG(N1‐H) . within hundreds of microseconds. This observation suggests that the generation of dG(N1‐H) . via dG(N2‐H) . following hydrogen atom abstraction from dG is unlikely to be a major pathway when HO . reacts with dG. Abstract : Guanine oxidation produces two major tautomeric 2′‐deoxyguanosin‐yl radicals—dG(N2‐H) . and dG(N1‐H) . . dG(N2‐H) . was independently generated from 1 . dG(N2‐H) . reacts significantly more slowly with thiol reducing agents than alkyl radicals. Contrary to previous reports, there is no evidence that dG(N2‐H) . rearranges to dG(N1‐H) . on the sub‐millisecond timescale.